SOME ACCOUNTING ASPECTS OF THE TAX EXEMPTION FOR FARMERS' COOPERATIVES. - Black, Martin L. (The Accounting Review, 1948)
Abstract The primary benefit accruing to farmers' cooperatives are the right to exemption from federal income taxes and the right to use the hank for cooperatives. Several federal statutes define and describe the prerequisites for these benefits. The most important of these provisions is found in Section 101 of the internal-revenue code dealing with exempt organizations and, more specifically, paragraph 12. The exemption from federal taxation is not automatic and it is not sufficient that the organization qualify as a matter of operation and organization. Form 1028, Exemption Affidavit, must be filed with the U.S. Treasury Department and a definite letter must be received from the Department before the exemption is effective. This form is an informational form and requires data as to the provisions of by-laws, charter, marketing agreements, etc. If the request filed after the beginning of operations, a detailed balance sheet must be submitted as well as a "classified statement of the receipts and disbursements'' during the current year. Unless the Commissioner has determined that an organization is exempt, it must prepare and file an income-tax return for each taxable year of its existence. A large number of farmers' cooperatives are not tax exempt. Many associations may not be so organized as to meet the specific qualifications for exemption. In other cases the associations may prefer to have a nonexempt status if management and owners believe that it is more advantageous to be taxed than to meet the statutory conditions of exemption. It is possible for these associations to be organized and operated is such a way that there is little taxable income.